If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -8 = x + -4 Reorder the terms: -8 + 2x = x + -4 Reorder the terms: -8 + 2x = -4 + x Solving -8 + 2x = -4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -8 + 2x + -1x = -4 + x + -1x Combine like terms: 2x + -1x = 1x -8 + 1x = -4 + x + -1x Combine like terms: x + -1x = 0 -8 + 1x = -4 + 0 -8 + 1x = -4 Add '8' to each side of the equation. -8 + 8 + 1x = -4 + 8 Combine like terms: -8 + 8 = 0 0 + 1x = -4 + 8 1x = -4 + 8 Combine like terms: -4 + 8 = 4 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| (2x+98)-2=(7x+8)-2 | | 6x-4(3x+2)=10 | | 15x-1=7x+15+8x-2 | | 12+7k=-3(-3k-6) | | y=.08x | | x^2-10x=125 | | (x+1)(x+3)(x+5)(x+7)+15= | | 2b^2-(5a+1)b+(3a^2-a-10)= | | x*137=18000 | | -(3y-4)=-2y+9 | | 3m+2m-12=4m+2 | | x*82=19000 | | 2*g^2+10*g-4=0 | | -0.5y+1=31 | | 39-2m=-2-5(1+5m) | | 8x-7=-7x+8 | | 2x+6=x+y | | x-15-24=10 | | -3x+1=3x+19 | | 2*g^2+5*g+1=0 | | 10(2*3-x)-0.1(5x-30)=0 | | 5x+66=-6x | | 2(-2+7k)-3k=-39+6k | | 12x-8=8x+8 | | 6x-3=5x-4 | | 4x+28+x+24-8x+20=15x-6 | | 5/2+2m/9=59/18 | | 10x+3=11+8x+19 | | 96-45-x=45 | | .6(10x-2)+3=2-(3x+4) | | -1+1x=5 | | 60+4x-1=6x+11 |